Cms And Automated Internet Systems - Abdusattorova Mohinur Omonjon qizi (Genius Journals, 2022)
This article provides insights into the use of CMS systems in education. It is used in the management of Internet resources and its important aspects are mentioned. Here are some suggestions on how to look or get an appointment for CMS.
Keywords: CMS; internet resources; manipulation; web projects